PENERAPAN TEKNOLOGI PENGADUK DAN PENGERING UNTUK MENINGKATKAN PRODUKSI JELI JERUK SEGERAN - Suwandi, Dedi; Luthfi, Muhammad; Amat, Mohammad (Jurnal Pengabdian kepada Masyarakat (NADIMAS), 2024)
The orange fruit produced in the village of Segeran, Juntinyuat sub-district, Indramayu regency is very abundant during the main harvest. To utilize the BUMDes fruit, he immediately had the idea of ​​making orange jelly. Previously, all processes for making orange jelly still used manual methods, such as squeezing, stirring, cutting and drying the orange jelly. With these problems, an orange jelly mixer and orange jelly dryer were made to increase the production of orange jelly immediately. The initial process of mixing jelly ingredients using human hands was only capable of producing 10 kg per hour. The manual mixing process was replaced with a jelly dough mixer so that the capacity increased to 30 kg per hour. This stirrer is driven by a 180 watt single phase Houle motor with a 1:5 gearbox, setting the stirrer fin rotation speed to 100 rpm. Next is the drying process for the orange jelly, initially using solar heat which takes 7 days. This drying process is replaced with a jelly dryer which can reduce drying time from 7 days to 8 hours. The dryer uses 4 heaters with 900 watt power with a capacity of 15 kg per drying process at a temperature of 600C. With these two pieces of equipment, the production capacity for orange jelly immediately increased from the initial 10 kg per week to 90 kg per week.